Finite element analysis on femoral neck and intertrochanteric fractures - Chng, Li Sing (2019)
Hip fracture is one of the most commonly sustained fractures and the frequency is increasing with the aging population. Depending on the hip fracture location, it is classified into femoral neck fracture or intertrochanteric fracture. Therefore, the choice of implants needs to be selected appropriately. Two set of finite element analysis studies were performed to validate the finite element model of the femoral neck and intertrochanteric fractures. In simulation A, Sawbone (model #3403) with Ø6.5 mm non cannulated screws were used. Osteoporotic material properties were applied to the cancellous and cortical bone. A two fragments of the femoral neck fracture were created based on the Pauwel’s classification angle of 60° and progressive axial loading was applied to the femoral head until failure. The maximum vertical reaction force and axial stiffness were 654.67 N and 621.2 N/mm respectively. In simulation B, Sawbone (model #3403) with proximal femoral nail anti rotation (PFNA) was used. Both osteoporotic and non-osteoporotic material properties were applied to the cancellous and cortical bone. A four fragments of intertrochanteric fracture were created based on the AO classification 31A2.2 and progressive axial loading was applied to the femoral head. The axial stiffness for osteoporotic femur with medial fragment at the baseline was 877.2 N/mm, which is in a good agreement with published literature. From the baseline of the medial fragment, a distal extension of 40 mm, 80 mm and 120 mm were created. Only the axial stiffness of the 40 mm distal extension were found to be significantly lower than the baseline.